Faktor-faktor yang Memengaruhi Minat Santri pada Usaha Pertanian Hortikultura di Pondok Pesantren Al Kautsar 561 Kabupaten Tasikmalaya - Nuryaman, Hendar; Karyani, Tuti; Noor, Trisna Insan; Setiawan, Iwan (Universitas Galuh, 2024)
Efforts to regenerate agricultural Human Resources (HR) have seen the potential of Islamic boarding schools as a space for regeneration as a provider space. Agricultural education and training for santri is a breakthrough in efforts to develop santri and develop the regeneration of human resources so that they are interested in the agricultural sector. This research aims to analyze the factors that influence students' interest in business in the agricultural sector, especially horticulture cultivation at the Al Kautsar 561 Islamic Boarding School, Tasikmalaya Regency. This research uses a quantitative approach with correlational methods (multiple linear regression) and descriptive methods. This research used a survey method with tools in the form of questionnaires on 48 santri’s. The results of the research show that internal and external factors as well as students' interest in horticultural farming are in the high category. Then, internal factors and external factors of students have a significant influence on students' interest in horticultural farming at the Al Kautsar 561 Islamic Boarding School, Tasikmalaya Regency. This shows that the higher the value of the students' internal and external factors, the higher the students' interest in horticultural farming. Therefore, it is hoped that the development of regeneration of agricultural human resources through Islamic boarding schools will be in line with improving the quality of Islamic boarding school students' human resources so that it will have implications for high interest in the world of agriculture, especially horticulture.